The Influence of Islamic Education in Improving Religious Understanding and Social Ethics among Teenagers - Muhamad Jamaludin Alwasi; Muhamad Alfi Fadlilla; Risa Karundeng; Yayat Hidayat; Siti Aisah (CV Projurnal Mitra Publikasi, 2025)
Islamic education plays an important role in developing the character and personality of the younger generation, especially regarding religious understanding and social ethics. The science of Islamic education not only addresses the theoretical aspects of Islamic religious teachings, but also the question of how such education can be used to obtain good social behavior. In the modern context, the challenges faced by teenagers are increasingly complex, especially due to the negative impact of social media, globalization, and changes in moral values. The study aims to explore the impact of Islamic education on enhancing religious understanding and social ethics among teenagers, identifying key success factors and providing recommendations for improvement. The research method used in this research is a literature study method, this method is carried out by examining various literature studies needed in the research, data collection techniques using data such as journals, books, and web references. The results of this study reveal that, a good understanding of religion affects the attitudes and behavior of teenagers, in worshiping and interacting with others. Teenagers with a good understanding of religion will be more disciplined in carrying out religious teachings and wiser in facing social challenges. Then, teenagers who have social ethics in accordance with Islamic values will not only be teenagers who have noble characters and good personalities, but will also play an active role in creating a more harmonious, peaceful and just society. The success factors of Islamic education are, 1). Teaching quality, 2). Learning approach, and 3). Family environment.